Workaround-to-Innovation — Exploring Bottom-Up Process Re-Design - Beverungen, Daniel; Bartelheimer, Christian; Assbrock, Agnes; Löhr, Bernd (European Conference on Information Systems (ECIS))

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

RAWA. Der Kampf um Frauenbefreiung in Afghanistan - Vukadinovic, Vojin Sasa (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Response inhibition for the basketball pump fake - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Book of Abstracts of the 66th Conference of Experimental Psychologists)

Dielectric metasurface for wave-vector variant and circular polarization dependent transmission - Wetter, Helene; Gao, Wenlong; Rehberg, Falk; Wingenbach, Jan; Schumacher, Stefan; Zentgraf, Thomas (Proceedings of The 14th International Conference on Metamaterials, Photonic Crystals and Plasmonics)

Auditory Pointers: Spatial Navigation with Sounds - Berndt, Axel ({Forschungskolloquium zur Audiokommunikation})

Mozart-Dekonstruktionen: Genese einer KI-generierten Konzertmusik - Berndt, Axel ({Digitale Methoden in den Geisteswissenschaften. Herausforderungen und Chancen})

Personalizing real‐world problems: Posing own problems increases self‐efficacy expectations, intrinsic value, attainment value, and utility value - Schönherr, Johanna (British Journal of Educational Psychology)
Abstract Background Real‐world problems are important in math instruction, but they do not necessarily trigger students' task motivation. Personalizing real‐world problems by (1) matching problems to students' shared living environment (context personalization) and (2) asking students to pose their own problems (active personalization) might be two interventions to increase students' task motivation. Aim In the current study, we investigated the effects of context personalization and active personalization on students' self‐efficacy expectations, intrinsic value, attainment value, utility value, and cost. Sample The participants were 28 fifth‐ and sixth‐grade students who voluntarily took part in a six‐month afterschool program in which they posed problems with the aim of creating a math walk in their hometown. Method Using a within‐subjects design, at the end of the afterschool program, the students rated their self‐efficacy expectations and task values for four self‐developed problems associated with their hometown, four peer‐developed problems associated with their hometown, and four instructor‐provided problems associated with unfamiliar locations. Results Students reported higher self‐efficacy expectations, intrinsic value, attainment value, and utility value for active‐personalized than non‐personalized problems. To a lesser extent, context personalization promoted intrinsic value and attainment value. No effect was found for cost. Conclusions Active personalization (i.e. asking students to pose their own real‐world problems) is suited to enhance students' task motivation, specifically their self‐efficacy expectations, intrinsic value, attainment value, and utility value. Context personalization still boosts students' intrinsic value and attainment value. Implementation in classroom instruction is discussed.

Rough, Rougher, Roughest: Extending EL with a Hierarchy of Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Proceedings of the 37th International Workshop on Description Logics (DL 2024), Bergen, Norway, June 18-21, 2024)

Preservice teachers' judgments of students’ expectations of success and task values: Close relations with their personal task motivation - Schönherr, Johanna; Schukajlow, Stanislaw (Teaching and Teacher Education)

Learning with visualizations helps: A meta-analysis of visualization interventions in mathematics education - Schönherr, Johanna; Strohmaier, Anselm R.; Schukajlow, Stanislaw (Educational Research Review)

Anxiety Moderates the Effects of Drawing Support on Drawing Accuracy in Mathematical Modeling - Schönherr, Johanna; Mayer, Richard E. (Lecture Notes in Computer Science)

Poverty/Poor - Breuer, Saskia Rebecca (Encyclopedia of the Bible and its Reception)

Vom Benutzen der Historie für Ideologeme der Gegenwart. Anmerkungen zu Schlesingers Überlegungen zum „Kampf der Schulen“ - Vukadinovic, Vojin Sasa (Die Wir-gegen-die-Gesellschaft. Warum der von Arthur M. Schlesinger vor 30 Jahren diagnostizierte Samen der identitätspolitischen Spaltung aufgegangen ist)

Siebter Oktober Dreiundzwanzig. Einleitung - Vukadinovic, Vojin Sasa (Siebter Oktober Dreiundzwanzig)

Editorial - Bartels, Mette; Vukadinovic, Vojin Sasa (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Editorial. Siebter Oktober Dreiundzwanzig - Barberi, Alessandro; Serloth, Barbara; Vukadinovic, Vojin Sasa (ZUKUNFT. Die Diskussionszeitschrift für Politik, Gesellschaft und Kultur)

Siebter Oktober Dreiundzwanzig (ZUKUNFT. Die Diskussionszeitschrift für Politik, Gesellschaft und Kultur)

Antisemitismus (Medienimpulse. Beiträge zur Medienpädagogik)

Mathematical Structures - Hilgert, Joachim